Cardiorespiratory Capacity of Papuan Sports Students: What is the Cardiorespiratory Capacity of Papuan Sports Students? - Prasetyo, Muhammad Teguh; Putra, Miftah Fariz Prima; Babingga, Harianto (Bima Loka: Journal of Physical Education, 2025)
The purpose of this study was to measure the cardiorespiratory endurance of college students through the Multistage Fitness Test (Beep Test) and VO₂Max calculation to obtain an objective picture of their aerobic fitness level. This study used a survey method involving two groups, namely male and female students. In the male group (n=12), the results showed that the majority of participants were in the below average category (66.7%), while 16.65% were in the low category and another 16.65% were in the average category. These findings indicate that most male students have cardiorespiratory capacity that still needs to be improved to achieve ideal fitness standards. Meanwhile, in the female group (n=4), all participants were in the low category with a percentage of 100%. This condition indicates that the aerobic fitness level of female students is still at a level far from optimal. Overall, the results of the study show that most students, both male and female, have aerobic fitness in the low to moderate category. These findings provide an important basis for planning a more targeted aerobic exercise program to improve the cardiorespiratory capacity of Papuan sports students.